Work Family Conflict and its Implications, Could Policewomen Cope? - Debbie Novia Rizal; Yulihasri Yulihasri; Donard Games (Institute of Computer Science (IOCS), 2022)
This study aims to identify the work family conflict experienced by the Police and its implications or involvement in work stress, work-life balance and psychological wellbeing, especially during the Covid-19 pandemic, as well as identify strategies for overcoming work family conflict so as to reduce negative impacts. This study used a qualitative approach by conducting semi-structured interviews with 5 policemen who were married and had children with an age range of 2-15 years and worked in the operational field. Data analysis was carried out with thematic analysis and using NVIVO 12 software. The results of this study found that police felt the impact of work family conflict physically such as fatigue, headache or fever or psychically such as sadness, easier emotions, feeling burdened with responsibilities in the office and at home in addition to the unbalanced division of time between work and family. Contrary to the impact felt, the police officers feel happy and proud of the multi-role conditions they have because being a policeman is their ideal from the beginning so that the risk of facing work family conflict has been prepared from the beginning. The combination of problem focused coping and emotion focused coping is a strategy to deal with work family conflict and its implications for work stress, work-life balance and psychological wellbeing. Such as time management, support from superiors, help from family and getting closer to the religious side. Especially during the Covid-19 pandemic, where school children learn online which requires the presence of parents to accompany children to study at home, the flexibility of working time in the office is needed by police.